2017
DOI: 10.1002/app.44984
|View full text |Cite
|
Sign up to set email alerts
|

Structural effects on the reprocessability and stress relaxation of crosslinked polyhydroxyurethanes

Abstract: Crosslinked polyhydroxyurethane (PHU) networks synthesized from difunctional six‐membered cyclic carbonates and triamines are reprocessable at elevated temperatures through transcarbamoylation reactions. Here we study the structural effects on reprocessability and stress relaxation in crosslinked PHUs. Crosslinked PHUs derived from bis(five‐membered cyclic carbonates) are shown to decompose at temperatures needed for reprocessing, likely via initial reversion of the PHU linkage and subsequent side reactions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
138
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(144 citation statements)
references
References 63 publications
5
138
0
Order By: Relevance
“…16 Recent studies have reported the dissociative reversible aminolysis reaction in PHU reprocessability process; however, no detailed mechanism has been discussed. 50,52 Our study suggests that urea formation occurred in presence of basic catalysts. A mechanism has been proposed, as illustrated in Scheme 2.…”
Section: Effect Of Organocatalysts On the Polymerization Kinetics Durmentioning
confidence: 66%
“…16 Recent studies have reported the dissociative reversible aminolysis reaction in PHU reprocessability process; however, no detailed mechanism has been discussed. 50,52 Our study suggests that urea formation occurred in presence of basic catalysts. A mechanism has been proposed, as illustrated in Scheme 2.…”
Section: Effect Of Organocatalysts On the Polymerization Kinetics Durmentioning
confidence: 66%
“…52 Dichtel, Hillmyer and coworkers also reported a comparable effect in hydroxyurethane vitrimers, in which an ether based-vitrimer displayed an E a of about 100 kJ mol À1 while a corresponding aliphatic-based material generated a higher energy barrier of 136 kJ mol À1 . 53 A similar comparison was done by Torkelson and co-workers in hydroxyurethane vitrimers. 55 Three different vitrimers, constituted of polybutadiene (PB), poly(tetramethylene oxide) (PTMO), and polydimethylsiloxane (PDMS), have been evaluated and compared with regard to their recycling efficiency.…”
Section: Network Composition or Vitrimer 'Solvent' Effectsmentioning
confidence: 72%
“…Moreover, the toughness of cross-linked polyurea could be significantly improved from 0.63 to 74.17 MJ m −3 and 124.17 MJ m −3 through incorporating 9.7% and 14.6% noncovalently bonded monomers, respectively, which is very prominent among the reported recyclable cross-linked thermosets. [7,11,12,[14][15][16]27,44,46,[48][49][50][51][52][53][54][55][56][57] Therefore, CSPU with superior toughness, remarkable solvent resistance, high transparency, and excellent multiple recyclability was achieved through the strategy of incorporating noncovalent bonds into main-chains.…”
Section: Doi: 101002/adma202000096mentioning
confidence: 99%